Best trigonometric and bilinear approximations for the classes of (ψ, β) -differentiable periodic functions - Shkapa, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish the exact-order estimates for the best m-term trigonometric approximations of the classes L^ψ_β, 1 in the space L_q, 2 < q < ∞. We also determine the exact orders of the best bilinear approximations for the classes of functions of two variables generated by functions of a single variable from the classL^ψ_β, p by the shifts of the argument in the space L_q_1,q_2, 1 ≤ q_1, q_2 ≤ ∞.